2012
DOI: 10.1142/s1793984412410061
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Cellular Uptake of Cellulose Nanocrystals

Abstract: There is growing evidence that filamentous nanoparticles offer advantages over spherical ones in drug delivery applications. The purpose of this study was to assess the potential of rod-like, plant-derived cellulose nanocrystals (CNCs) for nanomedical uses. Besides a nonspherical morphology, their facile bioconjugation, surface hydrophilicity and small size render CNCs promising drug carriers. The cytotoxicity of CNCs against nine different cell lines (HBMEC, bEnd.3, RAW 264.7, MCF-10A, MDA-MB-231, MDA-MB-468,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(137 citation statements)
references
References 40 publications
6
131
0
Order By: Relevance
“…The cellular uptake of nanocrystals may occur by either receptor-mediated or nonspecific endocytosis. 51 The former, likely the clathrin-and caveolae-mediated endocytosis, …”
Section: In Vitro Cytotoxicity Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The cellular uptake of nanocrystals may occur by either receptor-mediated or nonspecific endocytosis. 51 The former, likely the clathrin-and caveolae-mediated endocytosis, …”
Section: In Vitro Cytotoxicity Studymentioning
confidence: 99%
“…22,51 The surface charge of the nanocrystals implies an important role in the cellular uptake. Mahmoud et al 52 proved that the cellular uptake of positively charged cellulose nanocrystals via human embryonic kidney 293 was superior to that of the negatively charged one.…”
Section: Disclosurementioning
confidence: 99%
“…Dong and colleagues have shown cellular uptake after exposure to fluorescently labeled CNCs solely in the read-out of a fluorescent plate reader without visualizing the CNC−cell interaction. 17 Mahmoud et al showed uptake of FITC or rhodamine functionalized flax-derived CNCs depending on their surface charge. 66 However, due to the lack of sufficient microscopic analysis in 3D, the observed fluorescence could also stem from CNCs attachment to the outer cell membrane.…”
Section: 36mentioning
confidence: 99%
“…Furthermore, CNCs have been shown to be noncytotoxic to a multitude of cell types at concentrations as high as 50 µg/ml (18,19). CNCs are rodshaped particles which are relatively simple and inexpensive to produce, and their size is readily controlled via sulfuric acid hydrolysis (18,20,21).…”
Section: Technology In Cancer Research and Treatment 2014 April 16 Epumentioning
confidence: 99%